The association between Learner Education Disruption (LED) and Mental Health Outcomes of Primary Caregivers (15 Years and Older) During COVID-19 in South Africa - Andrady, Mabel Judith (University of the Witwatersrand, Johannesburg, 2023)
Background Mental illness affects around one-third of South Africans (Herman et al., 2009). With schools shut down during COVID-19, learners have either had to adapt to online/remote learning or have entirely dropped out of school. Many parents of these learners have had to deal with unemployment, no income, shortage of food, and possible bills to pay, including medical, with less or no access to government grants. This has further led to adverse mental health outcomes for students and parents/caregivers. Hence, further study is necessary to ascertain the impact of factors, such as pre-existing negative mental health, socioeconomic status, and their children's academic performance, on the overall mental well-being of individuals during the pandemic. Objective To examine the association between learner education disruption (LED) of adults 15 years and older, specifically primary caregivers, during COVID-19 in South Africa. Methodology The study used the National Income Dynamics Study – Coronavirus Rapid Mobile (NIDS-CRAM) Wave 5 Survey, and it focused on South African adults (15 years and older) who were primary caregivers and may have experienced LED. An unweighted total of 3019 primary caregivers responded to if they had any learners in their households who had not returned to school in the past year. The study's dependent variable is the mental health outcome that results from the absence of learner education. From this, a total of 350 participants responded “yes.” The outcome variable for this study is mental health. The outcome was measured by coding participants' responses to questions ga19 and ga20 as "1" for "yes" responses indicating little interest in doing things and feeling down, depressed, or hopeless and "0" for "no" responses. A new variable, mental_health_out, was then calculated by tabulating the "yes" responses from both questions. Demographic, socioeconomic, and COVID-19-related characteristics are the independent variables. The demographic variables include age, race, sex, and residency. The socioeconomic variables include education, access to school meals, and government grants received. The COVID-19-related variables are changes in income, mental health symptoms, and COVID-19 relief grants received. The rate of LED was calculated, and a chi-square test was run, followed by the adjusted binary logistic regression model performed. Results More women (69.55%) than males (30.44%) responded that having had poor mental health outcomes expressed having mental health outcomes. Furthermore, 34.91% of primary caregivers experienced LED with poor mental health outcomes from iT. Meanwhile, 63.14% who did not experience LED also suffered from poor mental outcomes. The adjusted logistic regression model for LED revealed that the odds of respondents having mental health outcomes decreased (OR= 0.91; CI: 0.72- 1.15), indicating that it is less likely that the event of poor mental health outcomes will occur. Conclusions The results of this study draw light to the importance of addressing the mental health outcomes of primary caregivers during education disruptions in South Africa; several program and policy recommendations are proposed in line with the South African Mental Health Framework.
A research report submitted to the Faculty of Humanities, Schools of Social sciences and Public Health, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Art in the field of Health Demography, in 2023.
Keywords: Mental Health Outcomes; Learner Education Disruption; Primary Caregivers; South Africa; Social Determinants of Health; UCTD